Spatial physical activity patterns among primary school children living in neighbourhoods of varying socioeconomic status: a cross-sectional study using accelerometry and Global Positioning System - Rahel Bürgi; Laura Tomatis; Kurt Murer; Eling D. de Bruin (BMC, 2016)
Abstract Background Neighbourhood socioeconomic status (SES) has been shown to be related to health status and overweight independent of individual SES. However, results about the association between neighbourhood SES and physical activity among children are ambiguous. Particularly, it is unknown how socioeconomic factors influence the spatial context of children's moderate-vigorous physical activity (MVPA) and sedentary behaviour (SB). This study aimed to investigate by means of Global Positioning System (GPS) and accelerometry whether locations where children engage in MVPA and SB differ by neighbourhood SES. Methods Participants included 83 children aged 7-9 from nine public schools located in a low- and high-SES area in Zurich, Switzerland. Children wore an accelerometer and GPS sensor for seven consecutive days. Time-matched accelerometer and GPS data was mapped with a geographic information system and each data point assigned to one of eight activity settings. The amount and proportion of MVPA and SB were calculated for every setting. To investigate differences between the two SES groups, multilevel analyses accounting for the hierarchical structure of the data were conducted. Results Both SES groups achieved most minutes in MVPA at own school, on streets and at home and recorded the highest proportions of MVPA in recreational facilities, streets and other schools. The highest amounts and proportions of SB were found at home and own school. High-SES children accumulated significantly more minutes in MVPA and SB in parks, sport facilities, other schools and streets, while the low-SES group spent more time in both activities in other places. When taking the total time spent in a setting into account and using the proportion of MVPA or SB, the only differences between the two groups were found at other schools and outside, where the high-SES children showed a significantly higher activity level (p-values <0.001). Conclusions Several differences in the spatial activity pattern between children from low- and high-SES neighbourhoods were found, independent of their individual SES. The findings seem to highlight the importance of providing safe streets and access to appropriate types of recreational facilities to reach recommended PA levels. Further policies to reduce SB within home and school environment are needed.